2013
DOI: 10.1111/ggi.12119
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perceived health and quality of life by activity status in community‐dwelling older adults

Abstract: Activity status was associated with self-perceived health status, but not with QoL. This study draws attention to the need of considering the activity of older adults for actions aimed at maintaining and improving their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
3
22
0
3
Order By: Relevance
“…Engaging in cognitively stimulating activities or group social activities and a high level of social support were associated with a better HRQL. In line with our results, a previous Spanish study on community-dwelling adults aged ≥60 found that social support, measured with DUFSS, had a positive effect on HRQL [13]. Similarly, in a German population-based cohort of 2443 people aged ≥75 years, a strong association was found between social support and HRQL (EQ-VAS) [43].…”
Section: Discussionsupporting
confidence: 91%
“…Engaging in cognitively stimulating activities or group social activities and a high level of social support were associated with a better HRQL. In line with our results, a previous Spanish study on community-dwelling adults aged ≥60 found that social support, measured with DUFSS, had a positive effect on HRQL [13]. Similarly, in a German population-based cohort of 2443 people aged ≥75 years, a strong association was found between social support and HRQL (EQ-VAS) [43].…”
Section: Discussionsupporting
confidence: 91%
“…Por otro lado, nuestro estudio muestra una relación negativa del estado de salud con la edad, confirmando la evidencia empírica previa (Olsen y Dahl, 2007;Romero et al, 2010;Pino et al, 2014). Se obtiene una relación positiva respecto al nivel de estudios, confirmando evidencias anteriores en España (Karlsdotter et al, 2012;Pino et al, 2014), mientras que si bien las mujeres presentan valores menores en su estado de salud autopercibido, confirmando otros estudios (ej., Olsen y Dahl, 2007), esta relación negativa no es estadísticamente significativa.…”
Section: Discussionunclassified
“…Se obtiene una relación positiva respecto al nivel de estudios, confirmando evidencias anteriores en España (Karlsdotter et al, 2012;Pino et al, 2014), mientras que si bien las mujeres presentan valores menores en su estado de salud autopercibido, confirmando otros estudios (ej., Olsen y Dahl, 2007), esta relación negativa no es estadísticamente significativa. En lo que se refiere a una mayor utilización de servicios sanitarios, lógicamente, la misma está relacionada negativamente con el estado de salud percibido de los encuestados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The five values that were possible answers of each question (Supplementary materials -page 5) were summed up to produce a total score ranging from 11 to 55, following the same methodology used by others (Pino et al, 2014). Then, to be able to model it, we adjusted its distribution to a negative binomial using a new variable defined as the maximum of the index (55) minus the observed value.…”
Section: Mediator Indicatorsmentioning
confidence: 99%